2017
DOI: 10.1016/j.amjoto.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Parotid adenoid cystic carcinoma: Retrospective single institute analysis

Abstract: a b s t r a c t a r t i c l e i n f oArticle history: Received 10 February 2017 Available online xxxx Purpose: Adenoid cystic carcinoma (ACC) is a uncommon salivary malignant tumor. Our aim was to review our experience with parotid ACC, to identify clinical-pathological parameters predictive for outcome. Materials and methods: We retrospectively reviewed 228 patients affected by parotid gland carcinomas surgically treated at our Institution. Forty-four ACC were included in this study. Multivariate analysis ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…Due to the rarity of parotid SaCa, no related literature was available for studying prognostic factors. It was noted that perineural invasion was independently correlated with death, and a similar finding could also be seen in other parotid high‐grade malignancy . However, the common risk factors, such as tumor stage, node status, and radiotherapy, had little effect on the prognosis.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Due to the rarity of parotid SaCa, no related literature was available for studying prognostic factors. It was noted that perineural invasion was independently correlated with death, and a similar finding could also be seen in other parotid high‐grade malignancy . However, the common risk factors, such as tumor stage, node status, and radiotherapy, had little effect on the prognosis.…”
Section: Discussionmentioning
confidence: 54%
“…Shi et al reported that node metastasis and the preoperative House‐Brackmann grade were independent predictors of both RFS and DSS in parotid duct carcinoma. A recent article described that recurrences were mainly influenced by the presence of perineural invasion and nerve paralysis, whereas female gender and age < 50 years were predictors for good prognosis in patients with adenoid cystic carcinoma . Due to the rarity of parotid SaCa, no related literature was available for studying prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor: The “Parotid Gland”, out of all the salivary glands, is the one most frequently affected by neoplasms, accounting for approximately 75% in all cases. [ 1 ] These neoplasms are generally benign, with only 25% of them being malignant forms. [ 1 ] The percentage of distant metastases from salivary gland is relatively low, with their occurrence being associated with high-grade tumors.…”
mentioning
confidence: 99%